Agent-Based Modeling of Urban Residential Electricity Demand Incorporating EV Charging Behavior - Alaliyat, Saleh; Oucheikh, Rachid (39th ECMS International Conference on Modelling and Simulation, ECMS 2025, Catania, Italy, 2025-06-24 - 2025-06-27, 2025)
By 2050, electric vehicles (EVs) are expected to be 40% of all cars on the road1. In some countries like Norway, more than 90% of the new cars sold are electric2. This rise in EVs presents challenges to the current electricity infrastructure to meet this rapid increase in electricity demand. In this study, we simulate urban residential electricity demand using an agent-based model to investigate the effects of EVs' charging behavior on the electricity demand profile and how using smart charging behavior helps in reducing the peak demand pressure. The simulation results of different scenarios show how it can be effective to schedule the charging time in the off-peak.
Keywords: Agent-Based Modeling; Charging Behaviour; Electricity Demand; EV; Simulation